Reprofiling of full‐length phosphonated carbocyclic 2′‐oxa‐3′‐aza‐nucleosides toward antiproliferative agents: Synthesis, antiproliferative activity, and molecular docking study. (7th May 2017) - Bkhaitan, Majdi M.; Mirza, Agha Zeeshan; Abdalla, Ashraf N.; Shamshad, Hina; Ul‐Haq, Zaheer; Alarjah, Mohammed; Piperno, Anna
Abstract : A series of phosphonated carbocyclic 2′ ‐oxa‐3′ ‐aza‐nucleosides were synthesized via 1, 3 dipolar cycloaddition and evaluated for their in vitro antiproliferative activity against the growth of cancer cell lines (MCF‐7, A2780, HCT116) and normal non‐transformed fibroblast (MRC5) using MTT assay. Synthesized compounds exhibited antiproliferative activity in the micromolar range. Compounds 11b showed the highest activity against MCF‐7 cells (IC50 of 0.2344 μm ). Cell cycle analysis was performed for compound 11b on MCF7 cells showing arrest of cells in the S phase. Molecular docking of synthesized compounds confirmed high affinity of these compounds to two different receptors for anticancer nucleosides on dCK, namely the 1P5Z and 2ZIA, showing scores higher than the cognate ligand for all tested compounds. All synthesized compounds were evaluated according to the Lipinski, Veber, and Opera rules, and all of them passed the evaluation showing excellent features, superior to reference drugs. In addition, ADME for all the synthesized compounds was predicted through a theoretical kinetic study using thediscovery studio 3.1 software. Abstract : Series of phosphonated carbocyclic 2′‐oxa‐3′‐aza‐nucleosides were synthesized and evaluated for their in vitro antiproliferative activity against MCF‐7, A2780, HCT116, and MRC5 using MTT assay. Molecular docking confirmed high affinity to two different receptors for anticancer nucleosides namely 1P5Z and 2ZIA. ADME was predicted through a theoretical kinetic study.